Radiosynthesis and Evaluation of 5-[I]Iodoindol-3-yl-β--Galactopyranoside as a β-Galactosidase Imaging Radioligand - Marcian E. Van Dort; Kuei C. Lee; Christin A. Hamilton; Alnawaz Rehemtulla; Brian D. Ross (Molecular Imaging)
The synthesis and investigation of 5-[ 125 I]iodoindol-3-yl-β- d -galactopyranoside ([ 125 I]IBDG) as a radioligand for single-photon emission computed tomography (SPECT) imaging of β-galactosidase expression are described. No-carrier-added [ 125 I]IBDG was synthesized by a radioiododestannylation approach in > 75% overall radiochemical yield and > 99% radiochemical purity. [ 125 I]IBDG was evaluated as a substrate using β-galactosidase-expressing (D54L) and nonexpressing (D54) human glioma cell lines. A 24-hour incubation of this substrate with cultured cells revealed a 6.5-fold greater intracellular trapping of radioactivity in D54L cells compared with D54 cells. Systemic delivery of [ 125 I]IBDG in nude mice bearing D54L tumors failed to show significant trapping of radioactivity within these tumors by SPECT imaging. In contrast, intratumoral injection of the substrate resulted in efficient trapping of radioactivity in D54L tumors but not D54 tumors, resulting in clear SPECT visualization of the former tumor. Based on dynamic SPECT imaging and blood metabolite analysis, we conclude that although [ 125 I]IBDG is an efficient in vivo substrate for β-galactosidase, its rapid renal clearance hampers its intratumoral availability on systemic administration.